The South American retroarc foreland system: The development of the Bauru Basin in the back-bulge province - Menegazzo, Mirian Costa; Catuneanu, Octavian; Chang, Hung Kiang [UNESP] (Elsevier B.V., 2016)
The aim of this research is to understand the tectonic setting of the Bauru Basin. This basin in central eastern South America has been classified as intracratonic, but the basin-fill geometry, the involved subsidence mechanisms and the age of the deposits are poorly understood. In this work, the ranges of the fossil taxa are analyzed and ages are proposed for the lithostratigraphic units. Isopach maps were used to reconstruct the stratigraphic intervals of the basin fill. The stratigraphy of the Bauru Basin is compared with that of the adjacent basins, and the data are integrated with the available information on South American geodynamics. The fossil record indicates that sediment accumulated from the Cenomanian to early Paleocene, beginning after the Mochica Phase of the Andean orogeny. The basin-fill geometry demonstrates migration of the depocenter through time, which occurred simultaneously with migration of the Andean Basin and immediately after the orogenic events of the Peruvian Phase. We propose that the Bauru Basin is a component of a retroarc foreland system developed during the early stages of the Andean evolution and that it was developed in the back-bulge province of this system. The Andean Basin constitutes the foredeep depozone of this foreland system (including the Potosi, Oriente, Acre and Maranon basins). In addition, the Upper Cretaceous of the Parecis and Solimoes basins were likely also developed in the back-bulge province. The thickness of the Bauru accumulation indicates that other mechanisms might have overlapped the flexural subsidence in this back-bulge province. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Andean orogeny; Back-bulge; Late Cretaceous; Retroarc foreland system; Subsidence mechanisms